2018
DOI: 10.1021/acsnano.8b02261
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Control of Sub-nanometer 1D SnTe via Nanostructuring within Single-Walled Carbon Nanotubes

Abstract: Nanostructuring, e. g., reduction of dimensionality in materials, offers a viable route toward regulation of materials electronic and hence functional properties. Here, we present the extreme case of nanostructuring, exploiting the capillarity of single-walled carbon nanotubes (SWCNTs) for the synthesis of the smallest possible SnTe nanowires with cross sections as thin as a single atom column. We demonstrate that by choosing the appropriate diameter of a template SWCNT, we can manipulate the structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 57 publications
2
54
0
Order By: Relevance
“…Since the pioneering work by Hicks and Dresselhaus, efforts have also been focused on utilizing the sharp features in the low-dimensional density-of-states to improve the power factor as well [17,18]. Theoretical studies on the thermoelectric power factor of NWs showed that one-dimensional (1D) modes could provide power factor improvements even up to 30% [19][20][21][22]. Experimentally, however, this has not yet been achieved, because to observe the true 1D nature, one needs to consider NW diameters down to a few nanometers (as in the case of Si) [23].…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work by Hicks and Dresselhaus, efforts have also been focused on utilizing the sharp features in the low-dimensional density-of-states to improve the power factor as well [17,18]. Theoretical studies on the thermoelectric power factor of NWs showed that one-dimensional (1D) modes could provide power factor improvements even up to 30% [19][20][21][22]. Experimentally, however, this has not yet been achieved, because to observe the true 1D nature, one needs to consider NW diameters down to a few nanometers (as in the case of Si) [23].…”
Section: Introductionmentioning
confidence: 99%
“…B NSs with single-atom thickness have attracted great interest due to its extraordinarily optical, electronic, thermal and anisotropic mechanical properties [149]. As for SnTe NSs material, it has been considered as an ideal substitute for narrow bandgap nanomaterials with low toxicity and NIR optical activity [150]. In the following part, we will introduce biomedical applications of AM, B NSs and SnTe NSs respectively.…”
Section: Other Types Of 2d Nanomaterials For Biomedical Applicationsmentioning
confidence: 99%
“…One of many directions is given by so‐called “encapsulated PCMs,” where ultra‐small structures are confined within carbon nanotubes, and where other structural motifs and guiding principles may be present than in the known bulk phases. This has been computationally studied, for example, for the case of GeTe and the heavier homologue SnTe where experimental TEM images are available for comparison. In these systems, it would now be interesting to compare the bonding (that is, that of close atomic contacts within the ultrathin PCM wires) to the bonding situation in the bulk.…”
Section: Future Directionsmentioning
confidence: 99%